A Mission to the medieval Middle East - Bertrandon de la Broquière, ?-1459. (London)
xiv s., [1] y. harita, [2], 336 s.
Keywords: “Bertrandon de la Broquiere was esquire to Philip the Good, Duke of Burgundy. Philip had plans for a new Crusade to the Holy Land and as part of this plan he persuaded Bertrandon to undertake a pilgrimage to the Holy Land to gather intelligence. Bertrandon set off in 1432 disguised as a pilgrim but acting as a spy for Philip, noting important details of the military, political and cultural aspects of Mamluk and Ottoman lands. The resulting account of his travels, translated into English by Thomas Johnes in 1807, provides invaluable information on the region, including the military tactics of the Turks and the early use of gunpowder by the Mamluks. It is also one of the key documents for the history of the Crusades in the late medieval period“ --